2018
DOI: 10.3892/ol.2018.8609
|View full text |Cite
|
Sign up to set email alerts
|

miR‑449c inhibits migration and invasion of gastric cancer cells by targeting PFKFB3

Abstract: Abstract. microRNAs (miRNAs) are important regulators in the development and progression of human gastric cancer (GC). However, the expression and biological function of miR-449c in GC remains unknown. In the present study, miR-449c was demonstrated to be downregulated in GC tissues and cell lines compared with normal. Decreased miR-449c levels were associated with poor prognosis in GC patients. Overexpression of miR-449c inhibited migration and invasion in SGC-7901 cells, while inhibition of miR-449c enhanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
2
6
0
Order By: Relevance
“…It also plays critical roles in adjusting the biological processes of cancer cells. Current evidence suggests that miR-449c can be widely involved in tumor cell growth, migration, proliferation and apoptosis (Miao et al, 2013;Sandbothe et al, 2017;Chen, Wang & Yue, 2018). We found that miR-449c was also upregulated in the HG group.…”
Section: Discussionsupporting
confidence: 47%
“…It also plays critical roles in adjusting the biological processes of cancer cells. Current evidence suggests that miR-449c can be widely involved in tumor cell growth, migration, proliferation and apoptosis (Miao et al, 2013;Sandbothe et al, 2017;Chen, Wang & Yue, 2018). We found that miR-449c was also upregulated in the HG group.…”
Section: Discussionsupporting
confidence: 47%
“…In the area of gastric cancer, Feng et al reported that miR-518 suppresses the progression of gastric cancer by promoting cell apoptosis via targeting MDM2 (19). Therefore, miR-518 may be a promising therapeutic target for gastric promotes gastric cancer cell growth and inhibits apoptosis (23). Wang et al demonstrated that over-expression of miR-217 inhibits gastric cancer cell proliferation, invasion and promotes apoptosis via regulating geriatric palliative care 5 (GPC5), and could be a potential therapeutic target (24).…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al showed that overexpression of miR-128b inhibits cell proliferation, migration, and invasion, and promotes apoptosis in gastric cancer cells via down-regulating adenosine 2b receptor (A2bR) ( 22 ). Wu et al reported that up-regulation of miR-449c suppresses gastric cancer cell growth and promotes apoptosis, while down-regulation of miR-449c promotes gastric cancer cell growth and inhibits apoptosis ( 23 ). Wang et al demonstrated that over-expression of miR-217 inhibits gastric cancer cell proliferation, invasion and promotes apoptosis via regulating geriatric palliative care 5 (GPC5), and could be a potential therapeutic target ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…The aberrant expression of miRNAs have been identified to be closely associated to the occurrence of numerous types of human malignant tumor, in which they were reportedly involved in cell apoptosis, proliferation, the cell cycle and metastasis by altering post-transcriptional gene expression ( 20-22 ). miRNAs have been identified to serve as both oncogenes or tumor suppressor genes in tumorigenesis; for example, the abnormal expression of miRNAs, such as miR-146a ( 23 ), miR-375( 24 ) and miR-449c ( 25 ), was determined to be closely associated with gastric tumorigenesis. In addition, a significant association was reported between tumor budding and the downregulated expression levels of miRNAs, such as miR-148a ( 26 ) and miR-625-3p ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hazard suppressor genes in tumorigenesis; for example, the abnormal expression of miRNAs, such as miR-146a (23), miR-375 (24) and miR-449c (25), was determined to be closely associated with gastric tumorigenesis. In addition, a significant association was reported between tumor budding and the downregulated expression levels of miRNAs, such as miR-148a (26) and miR-625-3p (27).…”
Section: Univariate Cox Analysis Multivariate Cox Analysis ----------mentioning
confidence: 99%